Asesmen dan psikoedukasi untuk mengoptimalkan kemampuan adaptasi pada anak intellectual disability: Studi kasus - Saragih, Emma Fauziah (Jurnal Kesmas Prima Indonesia, 2024)
Intellectual Disability is a disability characterized by significant limitation both in intellectual an adaptive functioning. that occur during developmental period. This research aims to carry out assessments to identify conditions and problems in children with intellectual disabilities, as well as provide psychoeducation to parents and related parties in order to optimize their potential and adaptive abilities. This research uses a qualitative method with a case study type. Data collection was carried out through interview methods, observation of participants and families, as well as conducting psychological assessments. The participant in this study was a boy with a chronological age of 8 years 9 months and a mental age of 2 years 9 months. Participants were given a psychological assessment in the form of the Stanford Binet intelligence test and the AAMR Scale to identify their adaptive function. The research results showed that the psychological assessment was able to provide an overview of the participants' intellectual function and adaptive function. Apart from that, providing psychoeducation is effective in providing understanding and increasing awareness among parents and family members regarding participants' psychological conditions.